THE IMPACT OF COMPUTATIONAL TECHNOLOGIES ON LINGUISTICS - Nilufar Gulumboy Qizi, Madaminova (Antis Publisher, 2025)
Objective: This study explores the integration of information technologies in linguistics, emphasizing their role in analyzing digital data and fostering innovative computational models for linguistic analysis. It highlights the interplay between software development and linguistics in creating systems for educational, professional, and automated language processing, including lexical and phonetic aspects. Methods: The research focuses on examining computational linguistics, utilizing digital tools and systems to process linguistic data effectively. It reviews innovative approaches in knowledge acquisition and language analysis, emphasizing their practical applications in contemporary linguistic practices. Results: Findings indicate that the application of information technologies in linguistics enhances the adaptability and efficiency of language systems. This includes advancements in computational models capable of automatic language processing and analysis, reflecting modern trends in globalization and cultural activation. Novelty: : The study underscores the transformative impact of computational linguistics by bridging traditional linguistic methods with innovative digital tools. This approach not only facilitates practical data processing but also reshapes the way language is analyzed and understood in the context of modern technological and cultural dynamics.